Signaling pathways governing the pathobiological features and antifungal drug resistance of Candida auris - Hyunjin Cha; Doyeon Won; Yong-Sun Bahn (mBio)
ABSTRACT Candida auris is an emerging multidrug-resistant fungal pathogen that poses a significant global health threat. Since its discovery in 2009, C. auris has rapidly spread worldwide, causing severe infections with high mortality rates, particularly in healthcare settings. Its ability to persist in the environment, form biofilms, and resist multiple antifungal drugs underscores the urgent need to understand its pathogenicity mechanisms and associated signaling pathways. Such insights are crucial for elucidating its unique virulence traits and developing targeted therapeutic strategies. Current studies have identified several key pathways involved in its pathogenicity and antifungal drug resistance. The Ras/cAMP/PKA pathway regulates critical virulence factors, including thermotolerance, morphological plasticity, and biofilm formation. The mitogen-activated protein kinase (MAPK) and calcineurin pathways contribute to stress responses and antifungal drug resistance. The regulation of Ace2 and morphogenesis (RAM) pathway influences cell aggregation, while the target of rapamycin (TOR) pathway affects filamentous growth and biofilm development. However, the distinct characteristics of C. auris, such as its rapid environmental spread and clade-specific traits, warrant further investigation into additional signaling pathways. This review provides a comprehensive analysis of known signaling pathways associated with C. auris pathogenicity and antifungal drug resistance, integrating insights from other fungal pathogens. By synthesizing current knowledge and identifying research gaps, this review offers new perspectives on future research directions and potential therapeutic targets against this formidable pathogen.